IDENTIFIKASI FUNGI PELAPUK JARINGAN KAYU MATI YANG BERPERAN PADA PROSES BIODELIGNIFIKASI DI TAMAN HUTAN RAYA BUKIT BARISAN KABUPATEN KARO - Musa Bernando; Edy Batara Mulya; Nelly A (Peronema Forestry Science Journal, 2012)
Biopulping is environmental technology as pulping alternative technology. The objective of this research was to get involved fungi on dead wood delignification in Taman Hutan Raya Bukit Barisan. Sensus method used in two hectares sample area, then isolation, purify, and identification of fungi. The isolation show there are fourteen fungus involved on wood delignification and with Bavendamm test result show three fungus positive WRP they are Phanerochaetae sp., Trametes sp., Asterostroma sp. Keywords: Biodelignification,Bavendamm test, Phanerochaete sp., Trametes sp., Asterostroma sp.